Identification of 3CP-Degrading bacteria from marine sponge and its β-dehalogenase gene - Mohd Sufian, Nurul Hanani; M., Azrul Naim; Tengku Abdul Hamid, Tengku Haziyamin; Huyop, Fahrul Zaman; Abdul Hamid, Azzmer Azzar (2018)
Halogenated organic compounds, which are xenobiotics, are widely distributed in the environment due to their routine use in agricultural and industrial activities. Haloalkanoic substances like 2,2-Dichloropropionic acid (2,2-DCP) and 3-Chloropropionic acid (3CP) are synthetic halogenated compounds which are often used as active components in herbicides. In this study, bacteria isolate which designated as H4 was successfully isolated from marine sponge from Kuantan East Coastal area. This bacteria is capable of degrading 2,2DCP and 3CP as the sole carbon and energy source which was evident by their observed bacterial growth on solid and liquid minimal media containing 2,2-DCP and 3CP. Results showed that the bacteria grew well in 10mM 2,2-DCP and 3CP and achieved maximum growth after 96 hours for H4 strain. The isolated bacteria have been identified based on morphological assay, biochemical assay and 16S rRNA gene sequence analysis. All bacterial colonies formed cream yellow coloured, circular and convex shaped with smooth surfaces. Isolate was Gram positive bacteria and rod in shaped. The DNA sequences of the 3CP-degrading bacteria was obtained via sequencing process. In conclusion, haloalkanoic acid degrading bacteria has been successfully identified from sponge and based on the similarity, the 16S RNA gene sequences of the isolate was closely related to Bacillus species.